Kerukunan Umat Beragama: Relevansi Pasal 25 Piagam Madinah dan Pasal 29 UUD 1945 - Nurul Fajriah (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2019)
This article is a study of literature describing religious harmony: the relevance of Article 25 of the Medina Charter and Article 29 of the 1945 Constitution. The Medina Charter was made in the 7th century (classical century) and Article 29 of the 1945 Constitution was born in modern times, around the 20th century. Both have relevancy which states that every citizen is free to adhere to their respective religions. The plurality of society in Indonesia has similarities and differences from the plurality of society in Medina around 622 AD. The stability and harmony of religious communities in the Medina at that time was regulated in the Medina charter which is the constitution of the Medina state. Harmony among religious communities in Indonesia is also an important concern of the Indonesian government as stipulated in Article 29 of the 1945 Constitution. Freedom of religion is guaranteed by the state because the state believes that religious diversity is not a disintegrating factor for the Indonesian people.Abstrak: Artikel ini adalah kajian literatur yang mendeskripsikan kerukunan umat beragama: relevansi pasal 25 Piagam Madinah dan Pasal 29 UUD 1945. Piagam Madinah dibuat pada abad VII (abad klasik) dan pasal 29 UUD 1945 baru lahir pada zaman modern, sekitar abad XX. Keduanya memiliki relevansi yang menyatakan bahwa setiap warga negara bebas menganut agamanya masing-masing. Kemajemukan masyarakat di Indonesia mempunyai sisi-sisi persamaan dan perbedaan dengan kemajemukan masyarakat di Madinah sekitar tahun 622 M. Keberlangsungan dan keharmonisan umat beragama di negara Madinah pada waktu itu diatur dalam piagam Madinah yang merupakan konstitusi negara Madinah. Kerukunan antar umat beragama di Indonesia juga menjadi perhatian penting pemerintah dengan adanya kebijakan Negara Republik Indonesia dari segi agama yang tertuang dalam pasal 29 UUD 1945. Kebebasan beragama ini dijamin oleh negara karena keyakinan bahwa keberagaman agama tidak akan menjadi disentegrating factor bagi bangsa Indonesia